New record of Rhachoepalpus Olivaceus Townsend, 1908 (diptera: tachinidae) from Puebla, Mexico - Sánchez-García, Lorena; Barrios-Díaz, Benjamín; Vázquez-Huerta, Gloria; Méndez-Gómez, José; Hernández Zetina, Dulce; Equihua-Martínez, Armando (Instituto de Ecología, A.C., 2017)
This is the first record of Rhachoepalpus olivaceus Townsned, 1908 for the state of Puebla, Mexico. The record is based on several specimens found in northern Puebla, municipality of Capuluaque, specifically in Tetela de Ocampo. The specimens were determined with taxonomic keys and deposited in the Insect Collection of Colegio de Postgraduados, Montecillo, Mexico (CEAM).